International Myeloma Working Group updated criteria for the diagnosis of multiple myeloma - Rajkumar, S. Vincent; Hillengaß, Jens; Goldschmidt, Hartmut (The lancet. Oncology, 2014)
This International Myeloma Working Group consensus updates the disease definition of multiple myeloma to include validated biomarkers in addition to existing requirements of attributable CRAB features (hypercalcaemia, renal failure, anaemia, and bone lesions). These changes are based on the identification of biomarkers associated with near inevitable development of CRAB features in patients who would otherwise be regarded as having smouldering multiple myeloma. A delay in application of the label of multiple myeloma and postponement of therapy could be detrimental to these patients. In addition to this change, we clarify and update the underlying laboratory and radiographic variables that fulfil the criteria for the presence of myeloma-defining CRAB features, and the histological and monoclonal protein requirements for the disease diagnosis. Finally, we provide specific metrics that new biomarkers should meet for inclusion in the disease definition. The International Myeloma Working Group recommends the implementation of these criteria in routine practice and in future clinical trials, and recommends that future studies analyse any differences in outcome that might occur as a result of the new disease definition.